EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM SOLVING DAN PROBLEM POSING BERBANTUAN ALAT PERAGA DITINJAU DARI KREATIVITAS BELAJAR SISWA - Nurmaningsih Nurmaningsih (Jurnal Pembelajaran Matematika, 2013)
Abstract: This reaserch aimed to reveal the effect of a Problem Solving and a Problem Posing learning model assisting by media instrument to the mathematics achievement based on the students’ learning creativity. We used the second grade students of Junior High Schools in Pontianak as the population. This was a 3 x 3 factorial design quasi-experimental research. The techniques of data collection were a test, questionnaires and documentation method. The balance test, a prerequisite tests analysis (normality and homogeneity test), and hypothesis test using unbalanced two ways analysis of variance were the techniques of data analysis that used in this research. The result indicates: (1) a Problem Solving learning model assisting by media instrument gives the same mathematics achievement as a Problem Posing learning model assisting by media instrument, but it gives better mathematics achievement than a directed learning; Furthermore, there is no difference of mathematics achievement between a Problem Posing learning model assisting by media instrument and a directed learning; (2) the students with high, medium an low learning creativity have the same mathematics achievment; (3) for all category of the learning creativity, a Problem Solving learning model assisting by media instrument gives the same mathematics achievement as a Problem Posing learning model assisting by media instrument, but it gives better mathematics achievement than a directed learning; Furthermore, there is no difference of mathematics achievement between a Problem Posing learning model assisting by media instrument and a directed learning; (4) for all category of the learning models, the students with high, medium an low learning creativity have the same mathematics achievment.Key words : Problem Solving assisting by media instrument, Problem Posing assisting by media instrument, directed learning, learning creativity, mathematics achievement